Conserving biological diversity : - Braatz, Susan M. (World Bank, 1992)
The objective of this strategy paper is to identify the countries and areas in the Asia-Pacific region that should receive priority for the conservation of biodiversity, taking in to account the value of their biological diversity and the urgency for their protection,...